2012
DOI: 10.1038/pr.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal seizures and postneonatal epilepsy: a 7-y follow-up study

Abstract: Background: seizures are one of the most common symptoms of acute neurological disorders in newborns. This study aimed at evaluating predictors of epilepsy in newborns with neonatal seizures. Methods: We recruited consecutively 85 neonates with repeated neonatal video-electroencephalogram (eeG)-confirmed seizures between January 1999 and December 2004. The relationship between clinical, eeG, and ultrasound (Us) data in the neonatal period and the development of postneonatal epilepsy was investigated at 7 y of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 37 publications
9
62
1
1
Order By: Relevance
“…Minchom et al [21] reported a 9.8% incidence, but they only considered newborns at term followed up to 3 years. Studies that evaluated the outcome of neonates with seizures detected with video-EEG, have reported a rate of post-neonatal epilepsy similar to that of ours [22][23][24][25][26], higher [27][28][29][30][31] or lower [32], but with differences in selection criteria of patients and length of follow-up. Most studies used clinical criteria only, but this method might overrate the presence of NS, including sudden and purposeless body movements that may be nonconvulsive.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Minchom et al [21] reported a 9.8% incidence, but they only considered newborns at term followed up to 3 years. Studies that evaluated the outcome of neonates with seizures detected with video-EEG, have reported a rate of post-neonatal epilepsy similar to that of ours [22][23][24][25][26], higher [27][28][29][30][31] or lower [32], but with differences in selection criteria of patients and length of follow-up. Most studies used clinical criteria only, but this method might overrate the presence of NS, including sudden and purposeless body movements that may be nonconvulsive.…”
Section: Discussionsupporting
confidence: 48%
“…More recent studies confirmed these data [36] reporting an onset within the first year in 72% of cases. Recurrence of seizures outside the neonatal period was described by Bergman et al [37] in 26.9% of cases (in 50% within 8 months), and by our group [23] in 60% of cases.…”
Section: Incidence and Age At Onset Of Epilepsymentioning
confidence: 79%
“…4 This co-morbidity is particularly striking when epilepsy is considered as an outcome. 2,5,6 Indeed, it has been reported that 87% of neonates with previous NS who subsequently developed epilepsy, also presented with both mental retardation and cerebral palsy. 2 Whether or not NS have a role in adverse outcomes in the developing brain is still debated, 7 particularly their effect on neurocognitive outcome, regardless of the underlying aetiology.…”
Section: Introductionmentioning
confidence: 98%
“…2,5,6 Indeed, it has been reported that 87% of neonates with previous NS who subsequently developed epilepsy, also presented with both mental retardation and cerebral palsy. 2 Whether or not NS have a role in adverse outcomes in the developing brain is still debated, 7 particularly their effect on neurocognitive outcome, regardless of the underlying aetiology. 8 Furthermore, the relationship between NS and the development of epilepsy later in life is still unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation